Islamic Religion Role to Maintain the Community Health during the COVID-19 Pandemic: the Efforts of Realizing Integrated New Normal - Mardiyan Hayati (Journal of Islamic Studies and Society, 2023)
Abstract. The dichotomy of common and religious science influences the government and community to manage COVID-19 virus pandemic problems. COVID-19 problems do not only deal with health problems but also include political, economic, and religious problems. Despite the virus' origin and the community's comments, the government, community, and religious organizations unite to find solutions to the problems. This research applied literature research or library research with analytical and reflective contents. The results showed that normal life or a new normal era, applied to describe the behavioral pattern after the pandemic, could reach the core and the roots of the problems with integrated implementation. The applied approach should include various science, such as common and religious science, to solve COVID-19 problems and to prevent new problem emergence.